LEARNING ASSISTANCE WITH THE SILABA METHOD ON CHILDREN'S READING ABILITY - Widad Sarah Hanifah; Dakusta Puspitasari; Siswanto (Khidmatan, 2022)
Reading is an activity that is beneficial for everyone. The low interest in reading students greatly affects the quality and quality of education in Indonesia. Learning programs at the elementary school level, especially in the lower grades, are directed at building reading skills. This study aimed to determine the impact of the silaba method of learning assistance on the reading ability of elementary school-age children in Babadan 01 hamlet. The tutoring method used is the silaba method. To facilitate the program, learning media is used, namely letter box media. The method in this activity is to use an Asset-Based Community Development (ABCD) approach. The evaluation was carried out with tests given to children, as well as interviews with children's parents, to measure the results of the tutoring program that had been implemented. As a result of this service program, children who initially could not read became able to read. The implementation of this tutoring activity went smoothly without significant obstacles.